A continuously graded polyacrylamide-based organic hydrogel electrolyte directionally enriched with vinylphosphonic acid

CN122907754APending Publication Date: 2026-10-13NORTHEASTERN UNIV AT QINHUANGDAO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611017899.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-09
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

这些技术说明乙烯基膦酸作为电池材料或聚合物膜组分本身并非新的技术手段,但其通常以独立粘结剂相、均匀膜组分或预聚合聚乙烯基膦酸的形式存在,目前尚未针对水系锌金属负极反复沉积/剥离过程中Zn2+通量不均、枝晶生长及凝胶/锌界面脱粘问题进行空间定向设计

Benefits of technology

1、本发明并非简单地将乙烯基膦酸单体加入电池聚合物中,而是使乙烯基膦酸分子先通过其膦酸基与锌表面发生配位,再利用其乙烯基与丙烯酰胺和两性离子单体发生光共聚,使锌负极和凝胶主体通过配位键与共价网络共同连接,并使乙烯基膦酸衍生链段、两性离子链段和交联密度沿厚度方向同步递减。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122907754A_ABST
    Figure CN122907754A_ABST
Patent Text Reader

Abstract

The application provides a continuous gradient polyacrylamide-based organic hydrogel electrolyte for directional enrichment of vinyl phosphonic acid, and belongs to the technical fields of aqueous zinc ion batteries and gel polymer electrolytes. The application realizes the formation of a continuous covalent network of the zinc surface-coordinated vinyl phosphonic acid, the vinyl phosphonic acid in the gel, acrylamide and the zwitterionic monomer, and the construction of a triple continuous gradient with synchronous reduction of the vinyl phosphonic acid-derived phosphonic acid segment, the zwitterionic segment and the crosslinking density, through short-time coordination treatment of the zinc metal matrix surface vinyl phosphonic acid, in-situ pre-photocuring of the zinc side precursor, multi-stage precursor sequential laying, controlled interdiffusion of adjacent regions and overall photocuring. The application solves the problem that the conventional polymer gel and the zinc negative electrode mainly rely on physical adhesion and are prone to interface voids after long-term cycling, and forms a continuous network without macroscopic peelable interface, so as to simultaneously consider the zinc side chemical anchoring, ion flux regulation, mechanical constraint and low transmission resistance of the positive electrode side.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of aqueous zinc-ion batteries and gel polymer electrolytes, and in particular to a triple continuous gradient polyacrylamide-based organic hydrogel electrolyte with vinylphosphonic acid directionally enriched on the zinc negative electrode side, its preparation method, and its application. Background Technology

[0002] Aqueous zinc-ion batteries possess advantages such as high safety, low cost, abundant raw material sources, and environmental friendliness, showing promising application prospects in large-scale and flexible energy storage. While zinc metal anodes exhibit high theoretical specific capacity and low redox potential, repeated zinc deposition / stripping in aqueous electrolytes can easily lead to localized electric field concentration and Zn degradation. 2+ Problems such as uneven flux distribution, dendrite growth, hydrogen evolution, corrosion, and byproduct accumulation lead to increased interfacial impedance, decreased coulombic efficiency, and shortened cycle life.

[0003] Gel electrolytes can restrict the macroscopic flow of liquid electrolytes, improve the contact between electrodes and electrolytes, and alleviate leakage and dendrite penetration problems to some extent. Polyacrylamide hydrogels have advantages such as readily available raw materials, mild polymerization conditions, strong liquid absorption capacity, and easily adjustable network structure, making them an important candidate material for gel electrolytes in aqueous zinc-ion batteries. However, traditional polyacrylamide gels typically have a uniform composition and uniform crosslinking density throughout their thickness, making it difficult to simultaneously meet the requirements of high interfacial stability and high mechanical confinement on the zinc anode side and low ion transport resistance on the cathode side.

[0004] Increasing the overall crosslinking density of the gel enhances its resistance to deformation and dendrite penetration, but reduces its liquid absorption capacity and increases ion migration resistance; conversely, decreasing the overall crosslinking density may lead to insufficient mechanical stability of the gel. Introducing N,N-dimethylformamide into the polyacrylamide network can modulate the hydrogen bonding between water molecules and the Zn... 2+ In a localized solvation environment, zwitterionic monomers can improve the affinity of the gel for ions and regulate the ion distribution at the interface. However, even if the above components are uniformly dispersed throughout the gel, it is still not possible to spatially divide the work according to the different needs of the zinc anode interface and the cathode interface.

[0005] In existing technologies, vinylphosphonic acid or polyvinylphosphonic acid has been used as an electrode binder in lithium-ion batteries, a proton conduction membrane in fuel cells, or a solid polymer electrolyte membrane. Its main functions are typically particle bonding, surface coordination, proton conduction, anti-swelling, or improving the chemical durability of the membrane. These technologies indicate that vinylphosphonic acid as a battery material or polymer membrane component is not a new technology in itself, but it typically exists as an independent binder phase, a homogeneous membrane component, or prepolymerized polyvinylphosphonic acid. Currently, it is not specifically used for Zn during repeated deposition / stripping processes in aqueous zinc metal anodes.2+ Spatial orientation design was used to address issues such as uneven flux, dendrite growth, and gel / zinc interface debonding. Summary of the Invention

[0006] To address the aforementioned problems in existing technologies, this invention provides a continuous gradient polyacrylamide-based organic hydrogel electrolyte for the directional enrichment of vinylphosphonic acid. This electrolyte uses polyacrylamide as the main network and water and N,N-dimethylformamide as a mixed solvent. Vinylphosphonic acid is simultaneously used as a zinc surface coordination anchoring molecule and a copolymerizable gradient functional monomer, and the vinylphosphonic acid-derived phosphonic acid segments, zwitterionic polymeric segments, and crosslinking density decrease synchronously from the zinc negative electrode side to the positive electrode side.

[0007] This invention utilizes short-term coordination treatment of vinylphosphonic acid on the surface of a zinc metal matrix, in-situ pre-photocuring of zinc-side precursors, sequential laying of multi-level precursors, controlled interdiffusion in adjacent regions, and overall photocuring to enable the vinylphosphonic acid coordinated on the zinc surface to form a continuous covalent network with vinylphosphonic acid, acrylamide, and zwitterionic monomers in the gel. It also constructs a triple continuous gradient in which vinylphosphonic acid-derived phosphonic acid segments, zwitterionic segments, and crosslinking density decrease simultaneously.

[0008] The technical solution of the present invention is as follows: This invention first provides a continuous gradient polyacrylamide-based organic hydrogel electrolyte with directional enrichment of vinylphosphonic acid. The directional enrichment is achieved on the zinc anode side, and the continuous gradient refers to the simultaneous decrease of three structural parameters—vinylphosphonic acid-derived segment content, zwitterionic segment content, and crosslinking density—from the zinc anode side to the cathode side. The preparation method of the organic hydrogel electrolyte includes the following steps: S1. Preparation of water-organic mixed electrolyte: Dissolve zinc salt in deionized water, add N,N-dimethylformamide and mix well to obtain water-organic mixed electrolyte; Preferably, in step S1, the zinc salt is at least one of zinc trifluoromethanesulfonate, zinc sulfate, zinc chloride, or zinc perchlorate.

[0009] Preferably, in step S1, the volume fraction of N,N-dimethylformamide in the water-organic mixed electrolyte is 10%-30%, and the concentration of zinc salt dissolved in deionized water is 1.0-3.0 mol / L.

[0010] In step S1 above, a mixed solvent environment is constructed using water and N,N-dimethylformamide to balance the properties of Zn. 2+ Transport, gel flexibility and active water regulation.

[0011] S2. Prepare multi-gradient precursor solutions with different raw material component concentrations: Add acrylamide, photoinitiator, zwitterionic monomer 3-(N,N-dimethyl-N-(2-methacryloyloxyethyl)ammonium)propanesulfonic acid inner salt with different concentrations, vinylphosphonic acid monomer with different concentrations, and crosslinking agent N,N'-methylenebisacrylamide with different concentrations to the water-organic mixed electrolyte prepared in step S1 to obtain precursor solutions with different gradients. The concentrations of vinylphosphonic acid monomer, zwitterionic monomer, and crosslinking agent in each gradient precursor solution are simultaneously reduced from the negative electrode to the positive electrode. Preferably, in step S2, 0.15-0.40 g of acrylamide is added to every 1.00 mL of water-organic mixed electrolyte; the mass of the photoinitiator is 0.5%-2.0% of the mass of acrylamide.

[0012] Preferably, in step S2, the photoinitiator is at least one of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone, lithium phenyl (2,4,6-trimethylbenzoyl)phosphate, or α-ketoglutaric acid.

[0013] Preferably, in step S2, in the first gradient precursor solution closest to the negative electrode, the added mass of vinylphosphonic acid monomer is 0.5%-3.0% of the mass of acrylamide, the added mass of zwitterionic monomer is 10%-20% of the mass of acrylamide, and the added mass of crosslinking agent is 0.5%-1.5% of the mass of acrylamide; In the precursor solution of the last gradient closest to the positive electrode, the added mass of vinylphosphonic acid monomer is 0%-0.2% of the mass of acrylamide, the added mass of zwitterionic monomer is 0%-5% of the mass of acrylamide, and the added mass of crosslinking agent is 0.05%-0.30% of the mass of acrylamide. In the precursor solutions between the two gradients mentioned above, the concentrations of these three raw material components decrease sequentially from the negative electrode to the positive electrode.

[0014] In step S2 above, unpolymerized vinylphosphonic acid monomers are used in the gradient precursor configuration, while the amounts of vinylphosphonic acid monomers, zwitterionic monomers, and crosslinking agents are varied to obtain three unidirectional continuous gradients. Enrichment of vinylphosphonic acid on the zinc side is used to enhance interfacial bonding and regulate Zn. 2+ Distribution, reducing its content on the positive electrode side avoids the Zn content caused by the uniform distribution of phosphonic acid sites throughout the gel. 2+ Excessive binding increases resistance to phase migration.

[0015] S3. Zinc negative electrode surface phosphonation treatment: The surface of the zinc metal substrate, which serves as the negative electrode, is contacted with a surface treatment solution containing vinyl phosphonic acid monomer for 10-120 s to form a phosphonic acid group coordination anchoring underlayer on the zinc surface. This allows the phosphonic acid groups in the vinyl phosphonic acid to coordinate with the Zn-O sites and / or Zn-OH sites in the natural oxide / hydrogen hydride layer on the zinc surface, while retaining the vinyl groups that can participate in free radical polymerization. Preferably, in step S3, the surface treatment solution containing vinylphosphonic acid monomer uses a mixture of water and ethanol as a solvent, the mass fraction of vinylphosphonic acid monomer is 0.1%-2.0%, and the volume ratio of water to ethanol is 1:4-4:1.

[0016] Furthermore, in step S3, the zinc metal substrate is polished, cleaned, and dried before contacting the surface treatment liquid containing vinylphosphonic acid monomer.

[0017] Furthermore, in step S3, after contact with the surface treatment solution containing vinylphosphonic acid monomers, the pretreated zinc metal substrate is cleaned with water or ethanol to remove uncoordinated vinylphosphonic acid monomers and retain the coordinated molecules on the zinc surface. If the vinylphosphonic acid monomer content is too low, it is difficult to form continuous anchoring points; if the content is too high or the contact time is too long, it may cause excessive corrosion of the zinc surface.

[0018] In step S3 above, the phosphonic acid groups of the vinylphosphonic acid monomer undergo polydentate coordination with oxide sites and / or hydroxyl sites on the zinc surface, while retaining the subsequent polymerization activity of the vinyl group. Unlike the prior art's use of vinylphosphonic acid as an electrode particle binder or a homogeneous component of polymer films, step S3 of this invention only constructs a coordination initiation interface on the zinc metal surface that can continue to participate in copolymerization.

[0019] S4. Constructing a zinc-side chemically coupled prepolymer layer: The first gradient precursor solution closest to the negative electrode is directly coated onto the phosphonic acid-based coordination anchoring substrate obtained in step S3 and pre-cured to form a zinc-side chemically coupled prepolymer layer between the zinc metal substrate and the organic hydrogel electrolyte. Preferably, in step S4, the thickness of the wet film after coating with the first gradient precursor solution is 50-150 μm.

[0020] Furthermore, in step S4, pre-curing causes the vinylphosphonic acid located on the surface of the zinc metal matrix to undergo free radical copolymerization with acrylamide, zwitterionic monomer and vinylphosphonic acid monomer in the first gradient precursor solution, thereby forming a chemically coupled prepolymer layer without an independent binder layer or independent adhesive layer between the zinc metal matrix and the organic hydrogel electrolyte.

[0021] In step S4 above, the vinyl group of vinyl phosphonic acid coordinated to the zinc surface participates in free radical polymerization together with acrylamide, zwitterionic monomer and vinyl phosphonic acid monomer in the first gradient precursor, so that the coordination layer and the gel body are continuously connected through the same covalent network, instead of setting an independent binder phase or a pre-made polyvinyl phosphonic acid film between them.

[0022] S5. Construct a continuous concentration gradient: Following the order of high to low concentrations of vinylphosphonic acid, zwitterionic monomer, and crosslinking agent, the precursor solutions of the remaining concentration gradients are sequentially laid on the zinc-side chemically coupled prepolymer layer obtained in step S4 toward the positive electrode direction. After each layer of precursor solution is laid, it is allowed to stand for 30-120 seconds to allow the newly laid precursor solution to undergo controlled interdiffusion with the adjacent gradient region in front of it. Furthermore, in step S5, except for the first gradient precursor solution, the thickness of the single-layer wet film after the other gradient precursor solutions are laid is 150-350 μm, preferably 250-320 μm; the laying thickness of each grade of precursor solution can be adjusted according to the gradient level so that the total thickness of the gel electrolyte after photocuring is maintained in the range of 0.50-1.50 mm.

[0023] In step S5 above, clear interlayer boundaries are eliminated by limited interdiffusion, and the three parameters are kept to change monotonically. If the interdiffusion time is too long, vinylphosphonic acid and zwitterionic monomers will tend to be evenly distributed, thereby weakening the spatial division of labor.

[0024] S6. Overall photocuring: After all the precursor solutions of all concentration gradients have been laid, overall photocuring is performed to cause the polymerizable monomers in adjacent gradient regions to undergo cross-regional copolymerization and cross-linking, forming a continuous polyacrylamide network without macroscopic peelable interfaces, thus obtaining the directionally enriched vinylphosphonic acid continuous gradient polyacrylamide-based organic hydrogel electrolyte.

[0025] Preferably, in steps S4 and S6, the pre-curing and overall photocuring use wavelengths of 320-405 nm and irradiances of 5-30 mW / cm², respectively. 2 The light source is used for irradiation; in step S4, the irradiation time for pre-curing is 20-60 s; in step S6, the overall curing time is 5-15 min.

[0026] Preferably, in step S6, after the precursor solutions of all gradients are photocured, the total thickness of the resulting organic hydrogel electrolyte is 0.50-1.50 mm; when performing EDS line scanning or XPS depth analysis along the thickness direction from the negative electrode to the positive electrode, the signal intensity of P and S elements gradually decreases.

[0027] In step S6 above, the entire area is photocured to form a continuous network, avoiding interlayer delamination and additional interfacial impedance in simple bilayer gels.

[0028] In use, the region with high phosphonic acid groups, high zwitterion content, and high crosslinking density faces the zinc anode to simultaneously provide chemical adhesion, ion flux regulation, and mechanical confinement; the cathode side adopts low phosphonic acid groups, low zwitterion content, and low crosslinking density to maintain faster ion transport and cathode wetting.

[0029] This invention also provides a method for applying the directional enrichment of vinyl phosphonic acid in a continuous gradient polyacrylamide-based organic hydrogel electrolyte in an aqueous zinc-ion battery. The method involves placing a zinc foil with a zinc-side coupling prepolymer layer at the bottom of a battery mold in step S5, then sequentially laying precursor solutions of other concentrations on the zinc-side chemically coupled prepolymer layer towards the positive electrode and performing controlled interdiffusion, and finally demolding after overall photocuring in step S6 to obtain an integrated battery module consisting of a zinc metal matrix / phosphonic acid-based coordination anchoring region / triple gradient transition region / positive electrode-side conduction region.

[0030] The beneficial technical effects of this invention are as follows: 1. This invention does not simply add vinylphosphonic acid monomers to the battery polymer. Instead, it first coordinates vinylphosphonic acid molecules with the zinc surface through their phosphonic acid groups, and then uses its vinyl groups to photopolymerize with acrylamide and zwitterionic monomers. This allows the zinc anode and the gel matrix to be connected together with the covalent network through coordination bonds, and the vinylphosphonic acid-derived segments, zwitterionic segments, and crosslinking density decrease synchronously along the thickness direction.

[0031] Therefore, in this invention, the vinylphosphonic acid monomer does not serve as an independent electrode binder or a uniformly dispersed proton-conducting membrane component, but instead simultaneously performs the functions of zinc surface coordination anchoring and gel network copolymerization. This design eliminates the need for a separate binder layer or polyvinylphosphonic acid film layer between the zinc surface and the gel matrix, thus solving the problem of conventional polymer gels relying primarily on physical adhesion with the zinc anode and easily developing interfacial voids after long-term cycling. Furthermore, a continuous network without macroscopically peelable interfaces is formed through controlled interdiffusion of adjacent precursors, simultaneously achieving zinc-side chemical anchoring, ion flux regulation, mechanical confinement, and low transport resistance on the cathode side.

[0032] 2. This invention does not form an independent electrode binder layer, a particulate binder phase, or a pre-fabricated polyvinylphosphonic acid electrolyte membrane. Instead, it directly incorporates vinylphosphonic acid-derived structural units into the PAM / DMAPS continuous network, which avoids the additional impedance and immersion debonding introduced by independent interface layers.

[0033] 3. This invention constructs three continuous gradients—vinylphosphonic acid-derived phosphonic acid segments, zwitterionic segments, and crosslinking density—that decrease synchronously from the zinc anode side to the cathode side, enabling chemical anchoring of the zinc side and Zn...2+ Flux regulation and mechanical constraints, along with low transport resistance on the positive electrode side, enable spatial division of labor; this structure differs from the uniform incorporation of vinylphosphonic acid or polyvinylphosphonic acid in polymer films. Furthermore, controlled interdiffusion and cross-regional overall photopolymerization form a continuous transition network without macroscopically peelable interfaces. The characteristic signals of P elements and phosphonic acid groups, and S elements and sulfonic acid groups along the thickness direction can be detected by EDS line scanning or XPS depth analysis, with signal intensity gradually decreasing from the zinc negative electrode side to the positive electrode side. Local mechanical property gradients can be characterized by micro-compression or nanoindentation tests; the local modulus or hardness of the zinc negative electrode side region is higher than that of the positive electrode side region, gradually decreasing along the thickness direction. Both structural and mechanical aspects demonstrate that the vinylphosphonic acid segments, zwitterionic segments, and crosslinking density are not uniformly distributed.

[0034] 4. In addition to electrochemical performance, this invention can also evaluate interfacial stability through 90° peel strength, adhesion retention rate after immersion, and Rct growth rate before and after cycling. Specifically, the 90° peel strength and adhesion retention rate after immersion of the samples obtained by the method of this invention are higher than those in comparative experiments with samples lacking vinylphosphonic acid or with uniformly distributed vinylphosphonic acid, and the Rct growth rate after cycling is smaller. This demonstrates the stabilizing effect of zinc-side coordination anchoring and the prepolymer copolymer structure from both interfacial mechanical and electrochemical impedance perspectives. Furthermore, the preparation process of this invention mainly employs short-time surface treatment, solution preparation, sequential layup, and UV curing, requiring no high temperature or complex equipment, making it suitable for the preparation of integrated zinc foil / gel components.

[0035] 5. In the comparative experiments of this invention, under the condition that the total amount of vinylphosphonic acid added is basically the same, the electrochemical performance of the zinc anode side oriented gradient distribution is better than that of the uniform distribution of vinylphosphonic acid; after 500 h of cycling, the Rct of the Zn∥Zn symmetric cell increased from about 75 Ω to about 100 Ω, an increase of about 33.3%, which is lower than the 45.0%-84.2% of the comparative experiment. Its symmetric cell can be stably cycled for about 2000 h, and the capacity retention rate of the Zn∥MnO2 full cell after 1000 cycles is about 82.7%. The above results indicate that the performance improvement does not come solely from vinylphosphonic acid itself, but mainly from the synergistic effect of zinc surface coordination-covalent copolymerization coupling, oriented enrichment of vinylphosphonic acid on the zinc side, and the triple continuous gradient. Attached Figure Description

[0036] Figure 1 The graph shows the long-cycle performance of the Zn∥Zn symmetric cell assembled using the organic hydrogel electrolyte prepared in Example 1 in Test Example 1.

[0037] Figure 2 The rate performance diagram shows the Zn∥Zn symmetric cell assembled using the organic hydrogel electrolyte prepared in Example 1 in Test Example 1.

[0038] Figure 3 The AC impedance spectra of the Zn∥Zn symmetric cell assembled using the organic hydrogel electrolyte prepared in Example 1 before cycling and after 500 h of cycling are shown in Test Example 1.

[0039] Figure 4 The rate performance graph shows the Zn∥MnO2 full cell assembled using the organic hydrogel electrolyte prepared in Example 1 in Test Example 1.

[0040] Figure 5 The graph shows the long-cycle performance of the Zn∥MnO2 full cell assembled using the organic hydrogel electrolyte prepared in Example 1 in Test Example 1.

[0041] Figure 6 The graph shows the cycle performance of a Zn∥Zn symmetric cell assembled with a gel electrolyte that does not contain vinylphosphonic acid but has a bicontinuous gradient in zwitterionic chain segment content and crosslinking density, as shown in Comparative Example 1.

[0042] Figure 7 The AC impedance spectra of the Zn∥Zn symmetric cell assembled with a gel electrolyte that does not contain vinylphosphonic acid but has a bicontinuous gradient of zwitterionic chain segment content and crosslinking density in Comparative Example 1 are shown before cycling and after 500 h of cycling.

[0043] Figure 8 The graph shows the cycling performance of a Zn∥MnO2 full cell assembled with a gel electrolyte that does not contain vinylphosphonic acid but has a dual continuous gradient of zwitterionic chain segment content and crosslinking density, as shown in Comparative Example 1.

[0044] Figure 9 The cycling performance diagram shows the Zn∥Zn symmetric cell assembled with a gel electrolyte in which vinylphosphonic acid is uniformly distributed, as shown in Comparative Example 2.

[0045] Figure 10 The AC impedance spectra of the Zn∥Zn symmetric cell assembled with a gel electrolyte in which vinylphosphonic acid is uniformly distributed, before cycling and after 500 h of cycling, are shown.

[0046] Figure 11 The cycling performance of the Zn∥MnO2 full cell assembled with a gel electrolyte in which vinylphosphonic acid is uniformly distributed, as shown in Comparative Example 2.

[0047] Figure 12 The graph shows the cycle performance of the Zn∥Zn symmetric cell assembled with a gel electrolyte in Comparative Example 3, in which methacrylic acid was used instead of vinylphosphonic acid.

[0048] Figure 13 The AC impedance spectra of the Zn∥Zn symmetric cell assembled with a gel electrolyte in Comparative Example 3, in which methacrylic acid was used instead of vinylphosphonic acid, are shown before cycling and after 500 h of cycling.

[0049] Figure 14 The graph shows the cycling performance of the Zn∥MnO2 full cell assembled with a gel electrolyte in Comparative Example 3, in which methacrylic acid was used instead of vinylphosphonic acid.

[0050] Figure 15 The graph shows the cycle performance of a Zn∥Zn symmetric cell assembled with a gel electrolyte in Comparative Example 4 where the amount of vinylphosphonic acid added exceeds the preferred range.

[0051] Figure 16 The AC impedance spectra of the Zn∥Zn symmetric cells assembled with gel electrolyte in Comparative Example 4, where the amount of vinylphosphonic acid added exceeded the preferred range, are shown before cycling and after 500 h of cycling.

[0052] Figure 17 The cycling performance diagram shows the Zn∥MnO2 full cell assembled with a gel electrolyte in Comparative Example 4 where the amount of vinylphosphonic acid added exceeds the preferred range. Detailed Implementation

[0053] The present invention will now be described in detail with reference to the accompanying drawings and embodiments. Obviously, the described embodiments are merely some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

[0054] The following are typical but non-limiting embodiments of the present invention. Unless otherwise specified, all raw materials used are commercially sourced.

[0055] Example 1: This embodiment provides a triple continuous gradient polyacrylamide-based organic hydrogel electrolyte with directional enrichment of vinylphosphonic acid on the zinc anode side after preparing a four-level gradient precursor solution, and its related integrated battery assembly. The specific preparation method is as follows: S1. Preparation of water-organic mixed electrolyte: First, dissolve zinc trifluoromethanesulfonate in deionized water to prepare a 2.0 mol / L zinc trifluoromethanesulfonate aqueous solution. Then, take 0.80 mL of the prepared zinc trifluoromethanesulfonate aqueous solution and mix it with 0.20 mL of N,N-dimethylformamide to obtain 1.00 mL of water-organic mixed electrolyte.

[0056] S2. Prepare four gradient precursor solutions, based on adding 0.25 g of acrylamide to every 1.00 mL of water-organic mixed electrolyte. Each gradient of the precursor solution contains different concentrations of the following three raw material components, with their contents from the first to the fourth gradient being as follows: (1) Vinylphosphonic acid added in the form of unpolymerized monomers was 0.0050 g, 0.0025 g, 0.00125 g and 0 g, respectively, which were 2.0%, 1.0%, 0.5% and 0% of the mass of acrylamide; (2) The zwitterionic monomers are 0.0375 g, 0.0250 g, 0.0125 g and 0 g, respectively, which are 15%, 10%, 5% and 0% of the mass of acrylamide, respectively. The zwitterionic monomer is 3-(N,N-dimethyl-N-(2-methacryloyloxyethyl)ammonium)propanesulfonic acid inner salt; (3) The crosslinking agents N,N'-methylenebisacrylamide were 0.0025 g, 0.0015 g, 0.00075 g and 0.00025 g, respectively, which were 1.00%, 0.60%, 0.30% and 0.10% of the mass of acrylamide; In addition, 0.0025 g of photoinitiator was added to each gradient of the precursor solution, i.e., the mass of the photoinitiator added was 1.0% of the mass of acrylamide. The photoinitiator was 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone. After the raw materials were prepared, the precursor solutions of each gradient were stirred in the dark until clear, and then subjected to vacuum degassing.

[0057] S3. Surface phosphonation treatment of the zinc anode: An 80 μm thick zinc foil was sequentially lightly polished with fine sandpaper, cleaned with deionized water and ethanol, and dried. Then, the zinc foil was immersed in a 0.5% (w / w) water / ethanol mixture of vinylphosphonic acid monomer for 60 s (water to ethanol volume ratio 1:1), allowing the phosphonic acid groups to coordinate with the Zn-O and / or Zn-OH sites in the natural oxide / hydrogen hydroxide layer on the zinc surface, forming a phosphonic acid-coordinated anchoring underlayer on the zinc surface. After removal, it was rapidly rinsed with ethanol to remove uncoordinated molecules and dried under nitrogen.

[0058] S4. Constructing the zinc-side chemically coupled prepolymer layer: Immediately afterwards, the first gradient precursor solution is uniformly coated onto the phosphonic acid-based coordination anchoring underlayer on the zinc foil surface, controlling the wet film thickness to be 100 μm, and then subjected to an irradiation at a wavelength of 365 nm and an irradiation intensity of 15 mW / cm². 2 Pre-curing under ultraviolet light for 30 seconds allows the vinyl groups of the surface-coordinated vinyl phosphonic acid to co-polymerize with the polymerizable monomers in the first gradient precursor, forming a zinc-side chemically coupled prepolymer layer without an independent binder layer.

[0059] S5. Constructing a continuous concentration gradient: A zinc foil with a zinc-side coupling prepolymer layer is placed at the bottom of a flat-plate photocurable mold with an inner cavity thickness of 1.00 mm. The mold consists of a polytetrafluoroethylene spacer and a quartz cover plate. Second, third, and fourth gradient precursor solutions are sequentially laid on the zinc-side chemically coupled prepolymer layer towards the positive electrode. The wet film thickness of each layer of the second, third, and fourth gradient precursor solutions is controlled within the range of 280-320 μm, preferably about 300 μm. After each layer of precursor solution is laid, it is allowed to stand for 60 s to allow limited interdiffusion between adjacent precursor solutions.

[0060] S6. Overall light curing: After all the layers are laid, at a wavelength of 365 nm and an irradiance of 15 mW / cm²... 2 The entire structure is cured under ultraviolet light for 10 min to obtain the directional enrichment of vinyl phosphonic acid in a continuous gradient polyacrylamide-based organic hydrogel electrolyte. The total thickness of the entire structure after photocuring is about 1.00 mm. After demolding, an integrated battery module consisting of "zinc foil / phosphonic acid-based chemical anchoring region / triple gradient transition region / positive electrode side conduction region" is obtained.

[0061] Example 2: In this embodiment, a three-level gradient precursor solution is used to construct a triple continuous gradient organic hydrogel electrolyte that directionally enriches vinylphosphonic acid on the zinc anode side.

[0062] Based on the preparation method of Example 1, each precursor stage contained 0.80 mL of a 2.0 mol / L aqueous solution of zinc trifluoromethanesulfonate, 0.20 mL of N,N-dimethylformamide, 0.25 g of acrylamide, and 0.0025 g of photoinitiator. In the first, second, and third gradient precursors, the mass percentages of vinylphosphonic acid relative to acrylamide were 1.5%, 0.5%, and 0%, respectively; the mass percentages of zwitterionic monomers were 12%, 6%, and 0%, respectively; and the mass percentages of N,N'-methylenebisacrylamide were 0.80%, 0.40%, and 0.15%, respectively. The zinc surface treatment, pre-curing, diffusion, and overall curing conditions were the same as in Example 1.

[0063] Example 3: In this embodiment, a five-level gradient precursor is used to construct a triple continuous gradient organic hydrogel electrolyte with directional enrichment of vinylphosphonic acid on the zinc negative electrode side.

[0064] The amounts of water-organic mixed electrolyte, acrylamide, and photoinitiator in each stage of the precursor were the same as in Example 1. The mass percentages of vinylphosphonic acid relative to acrylamide in the five-stage precursors were 2.5%, 1.5%, 1.0%, 0.5%, and 0%, respectively; the mass percentages of zwitterionic monomers were 16%, 12%, 8%, 4%, and 0%, respectively; and the mass percentages of N,N'-methylenebisacrylamide were 1.00%, 0.70%, 0.45%, 0.25%, and 0.10%, respectively. The first-stage precursor was pre-cured for 40 s, and the remaining precursors were allowed to diffuse statically for 45 s per stage. After all stages were laid, the entire system was cured for 12 min.

[0065] Example 4: In this embodiment, a four-level gradient precursor solution is used to construct a triple continuous gradient organic hydrogel electrolyte that directionally enriches vinylphosphonic acid on the zinc anode side.

[0066] Based on the preparation method of Example 1, the difference is that a water-organic mixed electrolyte was constructed using 10% N,N-dimethylformamide by volume, which consisted of 0.90 mL of 2.0 mol / L zinc trifluoromethanesulfonate aqueous solution and 0.10 mL of N,N-dimethylformamide. The remaining zinc surface vinylphosphonic acid treatment, the amount of vinylphosphonic acid, zwitterionic monomer, N,N'-methylenebisacrylamide and photoinitiator added in each stage of the precursor, and the curing conditions were all the same as in Example 1.

[0067] Example 5: In this embodiment, a four-level gradient precursor solution is used to construct a triple continuous gradient organic hydrogel electrolyte that directionally enriches vinylphosphonic acid on the zinc anode side.

[0068] Based on the preparation method of Example 1, the difference is that a water-organic mixed electrolyte was constructed using 30% N,N-dimethylformamide by volume, namely 0.70 mL of 2.0 mol / L zinc trifluoromethanesulfonate aqueous solution and 0.30 mL of N,N-dimethylformamide. The remaining zinc surface vinylphosphonic acid treatment, the amount of vinylphosphonic acid, zwitterionic monomer, N,N'-methylenebisacrylamide and photoinitiator added in each stage of the precursor, and the curing conditions were all the same as in Example 1.

[0069] Example 6: This Example 6 is based on Example 1, with the following differences: the zinc salt used is 1.0 mol / L zinc sulfate; the photoinitiator is lithium phenyl (2,4,6-trimethylbenzoyl) phosphate, and 0.0020 g is added for every 0.25 g of acrylamide, which is 0.8% of the mass of acrylamide; the mass fraction of vinylphosphonic acid monomer in the zinc surface treatment solution is 0.2%; a 405 nm light source is used for pre-curing and overall curing, and the remaining raw material amounts and process conditions are the same as in Example 1.

[0070] Example 7: This Example 7 is based on Example 1, with the following differences: the zinc salt used is 1.5 mol / L zinc chloride; the photoinitiator used is α-ketoglutaric acid, and 0.00375 g is added for every 0.25 g of acrylamide, which is 1.5% of the mass of acrylamide; the mass fraction of vinylphosphonic acid monomer in the zinc surface treatment solution is 1.0%; the pre-curing time is 50 s and the overall curing time is 15 min, and the remaining raw material amounts and process conditions are the same as in Example 1.

[0071] Example 8: This Example 8 is based on Example 1, with the following differences: the zinc salt used is 2.5 mol / L zinc perchlorate; the photoinitiator is still 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone, and 0.0025 g of acrylamide is added for every 0.25 g of acrylamide; the mass fraction of vinylphosphonic acid monomer in the zinc surface treatment solution is 1.5%; the remaining raw material amounts and process conditions are the same as in Example 1.

[0072] Comparative Example 1: Except for not treating the zinc surface with vinylphosphonic acid and not adding vinylphosphonic acid to each stage of the precursor, the other formulations and preparation conditions were the same as in Example 1, to verify the interfacial stability when only zwitterionic segment gradient and crosslinking density gradient were used.

[0073] Comparative Example 2: The polishing, cleaning, and surface phosphonation steps of the zinc foil and the water / ethanol treatment solution containing 0.5% vinylphosphonic acid monomer were the same as in Example 1. To eliminate the influence of the difference in the total amount of vinylphosphonic acid added, a weighted calculation was performed based on the actual laying volume of each gradient precursor in Example 1 and the addition ratio of vinylphosphonic acid in each gradient. The amount of vinylphosphonic acid added in the first to fourth gradient precursors was set to 0.65% of the mass of acrylamide, so that the total amount of vinylphosphonic acid added in Comparative Example 2 was basically the same as that in Example 1. The other conditions were the same as in Example 1 to compare the performance difference between uniform distribution of vinylphosphonic acid and directional gradient distribution on the zinc negative electrode side.

[0074] Comparative Example 3: Zinc surface treatment was performed using methacrylic acid monomer in an equimolar amount to vinylphosphonic acid monomer, and various precursors were added. All other conditions were the same as in Example 1 to verify whether common carboxylic acid polymerizable monomers could replace the polydentate coordination anchoring effect of phosphonic acid groups.

[0075] Comparative Example 4: The amount of vinylphosphonic acid monomer added in the first gradient precursor was increased to 3.5% of the mass of acrylamide. The composition and preparation conditions of the remaining grades were the same as in Example 1 to verify the effect of vinylphosphonic acid monomer content exceeding the preferred range on ion transport and zinc surface stability.

[0076] Comparative Example 5: Based on Example 1, the difference is that the volume fraction of N,N-dimethylformamide is reduced to 5%, that is, 1.00 mL of water-organic mixed electrolyte is prepared by using 0.95 mL of zinc trifluoromethanesulfonate aqueous solution and 0.05 mL of N,N-dimethylformamide. The remaining raw material amounts and process conditions are the same as in Example 1, in order to investigate the effect when the organic solvent content is lower than the volume fraction range of 10% to 30% defined in this invention.

[0077] Comparative Example 6: Based on Example 1, the difference is that the volume fraction of N,N-dimethylformamide is increased to 35%, that is, 1.00 mL of water-organic mixed electrolyte is prepared by using 0.65 mL of zinc trifluoromethanesulfonate aqueous solution and 0.35 mL of N,N-dimethylformamide. The remaining raw material amounts and process conditions are the same as in Example 1, in order to investigate the effect when the organic solvent content is higher than the volume fraction range of 10% to 30% defined in this invention.

[0078] Comparative Example 7: Based on Example 1, the difference is that the mass fraction of vinylphosphonic acid monomer in the zinc surface treatment solution is reduced to 0.05%, the contact time is still 60 s, and the other raw material amounts and process conditions are the same as in Example 1, in order to investigate the effect when the concentration of vinylphosphonic acid monomer in the surface treatment solution is lower than the mass fraction range of 0.1% to 2.0% defined in this invention.

[0079] Comparative Example 8: Based on Example 1, the difference is that the controlled interdiffusion time after each layer of precursor solution is extended to 180 s, while the remaining raw material amounts and process conditions are the same as in Example 1, in order to examine the effect when the interdiffusion time exceeds the scope of the claims and the gradient tends to be homogenized.

[0080] The main process parameters of Examples 1-8 and Comparative Examples 1-8 are shown in Table 1 and Table 2 below, respectively.

[0081] Table 1 Summary of process parameters for Examples 1-8 Table 2 Summary of process parameters for Comparative Examples 1-8 Test Example 1: Electrochemical Performance Testing of Examples Batteries were assembled using the four-stage triple continuous gradient zinc anode-gel electrolyte integrated module prepared in Example 1. The Zn∥Zn symmetric cell was assembled with two of the aforementioned integrated zinc anode modules facing each other; the Zn∥MnO2 full cell was assembled with a manganese dioxide cathode and the aforementioned integrated zinc anode module. All cells underwent long-cycle, rate, and AC impedance testing under the following conditions: the phosphonate-based chemical anchoring region was directly bonded to the zinc anode, and the positive electrode-side conductive region faced the manganese dioxide cathode.

[0082] Long-cycle testing uses 1 mA cm -2 Current density and 1 mAh cm -2 The surface capacity was measured, with a total testing time of 2000 hours; the rate testing was conducted with a fixed surface capacity of 1 mAh cm⁻¹. -2 The current densities were 0.5, 1, 2, 4, 8, 4, 2, 1 and 0.5 mA cm⁻¹, respectively. -2 The AC impedance test frequency range is 100 kHz to 0.01 Hz, and the AC disturbance amplitude is 5 mV. The full cell test voltage range is 0.8 to 1.8 V, and the rate test current densities are 0.1, 0.2, 0.5, 1, 2, 4, and 0.1 A g, respectively. -1 Long-cycle testing at 1 Ag -1 Perform 1000 laps.

[0083] Figure 1 The image shows the long-cycle performance of a Zn∥Zn symmetric battery assembled using the phosphonic acid-based chemically anchored triple-gradient polyacrylamide-based organic hydrogel electrolyte prepared in Example 1. Figure 1 As shown, at 1 mA cm -2 and 1 mAh cm -2 Under these conditions, the symmetrical cell can cycle stably for 2000 hours, and the voltage polarization remains at a low level throughout.

[0084] Figure 2 The image shows the rate performance of a Zn∥Zn symmetric cell assembled using the phosphonic acid-based chemically anchored triple-gradient polyacrylamide-based organic hydrogel electrolyte prepared in Example 1. Figure 2 As shown, when the current density increases from 0.5 mA cm⁻¹ -2 Gradually increase to 8 mA cm -2 At that time, the polarization voltage increased from about 40 mV to about 110 mV; when the current density decreased again to 0.5 mA cm⁻¹ -2Afterwards, the polarization voltage basically returned to its initial level.

[0085] Figure 3 The AC impedance spectra of a Zn∥Zn symmetric cell assembled using the phosphonic acid-based chemically anchored triple-gradient polyacrylamide-based organic hydrogel electrolyte prepared in Example 1 are shown before and after cycling. Figure 3 As shown, the charge transfer resistance Rct before and after cycling is approximately 75 Ω and 100 Ω, respectively, with the impedance increasing only slightly after cycling.

[0086] Figure 4 The image shows the rate performance of a Zn∥MnO2 full cell assembled using the phosphonic acid-based chemically anchored triple-gradient polyacrylamide-based organic hydrogel electrolyte prepared in Example 1. Figure 4 As shown, at concentrations of 0.1, 0.2, 0.5, 1, 2, and 4 Ag... -1 The batteries can provide approximately 269, 223, 188, 156, 128, and 108 mAh g, respectively. -1 The specific capacity; when the current density recovers to 0.1 Ag -1 At that time, the specific capacity recovered to approximately 200 mAh g. -1 .

[0087] Figure 5 The image shows the long-cycle performance of a Zn∥MnO2 full cell assembled using the phosphonic acid-based chemically anchored triple-gradient polyacrylamide-based organic hydrogel electrolyte prepared in Example 1. Figure 5 As shown, in 1 Ag -1 The initial battery capacity is approximately 200 mAh g. -1 After activation, the concentration increases to approximately 220 mAh g. -1 After 1000 cycles, it still maintains approximately 182 mAh g. -1 The capacity retention rate is approximately 82.7%, and the coulombic efficiency is close to 100%.

[0088] The performance of Examples 2-8 was tested using the same method, and the results are shown in Table 3.

[0089] Table 3 Electrochemical performance tests of Examples 1-8 Table 3 shows that the gradient order, the ratio of N,N-dimethylformamide, the type and concentration of zinc salt, the type of photoinitiator, and the concentration of surface phosphonate all affect interfacial impedance and cycling performance. Specifically, Example 1 with a four-level gradient achieves a good balance between interfacial stability and ion transport; Example 2 with a three-level gradient has weak gradient adjustment; and Example 3 with a five-level gradient, while close to Example 1, has increased process complexity. A DMF ratio of 10% provides insufficient control over active water, while 30% increases ion migration resistance. Different zinc salts and photoinitiation systems can still achieve the structure of this invention, but performance decreases with variations in salt type, concentration, and surface VPA concentration.

[0090] Test Example 2: Comparative Test of Vinylphosphonic Acid Distribution Pattern and Parameter Boundaries Example 1 and Comparative Examples 1-4 were compared under the same test conditions: Zn∥Zn symmetric cell cycling condition was 1 mA cm⁻¹. -2 and 1 mAh cm -2 The AC impedance test frequency range was 100 kHz-0.01 Hz, with an AC disturbance amplitude of 5 mV. Tests were conducted before cycling and after 500 hours of cycling. The Zn∥MnO2 full cell was tested in the voltage range of 0.8-1.8 V and at 1 A g. -1 Cycle 1000 times at current density.

[0091] The electrochemical test results of Comparative Example 1 are as follows: Figure 6-8 As shown. At 1 mA cm -2 and 1 mAh cm -2 Under these conditions, the stable cycling time of the Zn∥Zn symmetric cell is approximately 950 h, with polarization gradually increasing in the later stages. The Rct before cycling and after 500 h of cycling are approximately 95 Ω and 175 Ω, respectively, representing an increase of approximately 84.2%. The Zn∥MnO2 full cell at 1 A g -1 The initial capacity is approximately 195 mAh. -1 The highest capacity after activation is approximately 208 mAh g. -1 After 1000 cycles, the capacity is approximately 145 mAh g. -1 The capacity retention, calculated based on the highest capacity after activation, is approximately 69.7%, and the stable coulombic efficiency is approximately 99.2%.

[0092] The electrochemical test results of Comparative Example 2 are as follows: Figure 9-11 As shown. At 1 mA cm -2 and 1 mAh cm -2 Under these conditions, the stable cycling time of the Zn∥Zn symmetric cell is approximately 1450 h. The Rct before cycling and after 500 h of cycling are approximately 100 Ω and 145 Ω, respectively, representing an increase of approximately 45.0%. The Zn∥MnO2 full cell at 1 A g... -1The initial capacity is approximately 190 mAh g. -1 The highest capacity after activation is approximately 205 mAh g. -1 After 1000 cycles, the capacity is approximately 158 mAh g. -1 The capacity retention rate is approximately 77.1%, and the stable coulomb efficiency is approximately 99.4%.

[0093] The electrochemical test results of Comparative Example 3 are as follows: Figure 12-14 As shown. At 1 mA cm -2 and 1 mAh cm -2 Under these conditions, the stable cycling time of the Zn∥Zn symmetric cell is approximately 800 h, after which the polarization increases significantly. The Rct before cycling and after 500 h of cycling are approximately 105 Ω and 190 Ω, respectively, representing an increase of approximately 81.0%. The Zn∥MnO2 full cell at 1 A g -1 The initial capacity is approximately 188mAh g. -1 The maximum capacity after activation is approximately 200 mAh g. -1 After 1000 cycles, the capacity is approximately 136 mAh g. -1 The capacity retention rate is approximately 68.0%, and the stable coulombic efficiency is approximately 98.9%.

[0094] The electrochemical test results of Comparative Example 4 are as follows: Figure 15-17 As shown. At 1 mA cm -2 and 1 mAh cm -2 Under certain conditions, the Zn∥Zn symmetric cell can cycle stably for approximately 1200 h, with polarization gradually increasing in the later stages. The Rct before cycling and after 500 h of cycling are approximately 112 Ω and 178 Ω, respectively, representing an increase of approximately 58.9%. The Zn∥MnO2 full cell at 1 A g -1 The initial capacity is approximately 198 mAhg. -1 The activated capacity is approximately 200 mAh g. -1 After 1000 cycles, the capacity is approximately 150 mAh g. -1 The capacity retention rate is approximately 75.0%, and the stable coulombic efficiency is approximately 99.2%.

[0095] Based on the combined results of Example 1 and Comparative Examples 1-4, it is evident that without vinylphosphonic acid, the interfacial impedance increases rapidly after cycling. While a uniform distribution of vinylphosphonic acid with a similar total amount improves interfacial stability, it remains weaker than the zinc-side oriented gradient distribution. When methacrylic acid is used as a substitute, the carboxylic acid groups struggle to achieve the same multidentate coordination-copolymerization coupling effect as the phosphonic acid groups. Excess vinylphosphonic acid increases initial impedance and reduces cycling performance. Therefore, the technical effect of this invention does not derive from the known role of vinylphosphonic acid as a general battery additive, binder, or membrane component, but rather from the synergistic effect of continuous copolymerization of surface-coordinated vinylphosphonic acid with the gel precursor, zinc-side oriented enrichment of vinylphosphonic acid, and the triple continuous gradient.

[0096] Comparative Examples 5-8 were used to investigate the effects of N,N-dimethylformamide content below the lower limit, N,N-dimethylformamide content above the upper limit, the concentration of vinylphosphonic acid treatment solution on the zinc surface below the lower limit, and the controlled interdiffusion time exceeding the upper limit, respectively. The four groups of samples were tested under the same conditions as described in Test Example 2, and the test results are shown in Table 4.

[0097] Table 4 Performance tests of Comparative Examples 1-8 As shown in Table 4, when the DMF content is too low, the regulation of water activity and solvation structure is insufficient, resulting in an increase in Rct after cycling and a decrease in the full cell capacity retention. When the DMF content is too high, the ion migration resistance in the gel increases, and both the initial Rct and the Rct after cycling increase significantly. When the surface VPA concentration is too low, there are insufficient coordination anchoring points on the zinc side, resulting in a decrease in interface stability. When the interdiffusion time is too long, the gradient tends to become uniform, weakening the spatial division of labor between zinc-side enhancement and low-resistance transport on the cathode side. Therefore, its stable cycling time and full cell capacity retention are both lower than those of Example 1.

[0098] Although the embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and embodiments. They can be applied to various fields suitable for the present invention. For those skilled in the art, and for those of ordinary skill in the art, various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principles and spirit of the present invention. Therefore, the present invention is not limited to the specific details without departing from the general concept defined by the claims and their equivalents.

Claims

1. A continuous gradient polyacrylamide-based organic hydrogel electrolyte for the directional enrichment of vinylphosphonic acid, characterized in that, The directional enrichment is directional enrichment on the zinc anode side, and the continuous gradient is the simultaneous decrease of the three structural parameters—vinylphosphonic acid derivative segment content, zwitterionic segment content, and crosslinking density—from the zinc anode side to the cathode side. The preparation method of the organic hydrogel electrolyte includes the following steps: S1. Preparation of water-organic mixed electrolyte: Dissolve zinc salt in deionized water, add N,N-dimethylformamide and mix well to obtain water-organic mixed electrolyte; S2. Prepare multi-gradient precursor solutions with different raw material component concentrations: Add acrylamide, photoinitiator, zwitterionic monomer 3-(N,N-dimethyl-N-(2-methacryloyloxyethyl)ammonium)propanesulfonic acid inner salt with different concentrations, vinylphosphonic acid monomer with different concentrations, and crosslinking agent N,N'-methylenebisacrylamide with different concentrations to the water-organic mixed electrolyte prepared in step S1 to obtain precursor solutions with different gradients. The concentrations of vinylphosphonic acid monomer, zwitterionic monomer, and crosslinking agent in each gradient precursor solution are simultaneously reduced from the negative electrode to the positive electrode. S3. Zinc negative electrode surface phosphonation treatment: The surface of the zinc metal substrate, which serves as the negative electrode, is contacted with a surface treatment solution containing vinyl phosphonic acid monomer for 10-120 s to form a phosphonic acid group coordination anchoring underlayer on the zinc surface. This allows the phosphonic acid groups in the vinyl phosphonic acid to coordinate with the Zn-O sites and / or Zn-OH sites in the natural oxide / hydrogen hydride layer on the zinc surface, while retaining the vinyl groups that can participate in free radical polymerization. S4. Constructing a zinc-side chemically coupled prepolymer layer: The first gradient precursor solution closest to the negative electrode is directly coated onto the phosphonic acid-based coordination anchoring substrate obtained in step S3 and pre-cured to form a zinc-side chemically coupled prepolymer layer between the zinc metal substrate and the organic hydrogel electrolyte. S5. Construct a continuous concentration gradient: Following the order of high to low concentrations of vinylphosphonic acid, zwitterionic monomer, and crosslinking agent, the precursor solutions of the remaining concentration gradients are sequentially laid on the zinc-side chemically coupled prepolymer layer obtained in step S4 toward the positive electrode direction. After each layer of precursor solution is laid, it is allowed to stand for 30-120 seconds to allow the newly laid precursor solution to undergo controlled interdiffusion with the adjacent gradient region in front of it. S6. Overall photocuring: After all the precursor solutions of all concentration gradients have been laid, overall photocuring is performed to cause the polymerizable monomers in adjacent gradient regions to undergo cross-regional copolymerization and cross-linking, forming a continuous polyacrylamide network without macroscopic peelable interfaces, thus obtaining the directionally enriched vinylphosphonic acid continuous gradient polyacrylamide-based organic hydrogel electrolyte.

2. The organic hydrogel electrolyte according to claim 1, characterized in that, In step S1, the zinc salt is at least one of zinc trifluoromethanesulfonate, zinc sulfate, zinc chloride, or zinc perchlorate.

3. The organic hydrogel electrolyte according to claim 1, characterized in that, In step S1, the volume fraction of N,N-dimethylformamide in the water-organic mixed electrolyte is 10%-30%, and the concentration of zinc salt dissolved in deionized water is 1.0-3.0 mol / L.

4. The organic hydrogel electrolyte according to claim 1, characterized in that, In step S2, 0.15-0.40 g of acrylamide is added to every 1.00 mL of water-organic mixed electrolyte; the mass of the photoinitiator is 0.5%-2.0% of the mass of acrylamide.

5. The organic hydrogel electrolyte according to claim 1, characterized in that, In step S2, the photoinitiator is at least one of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone, lithium phenyl (2,4,6-trimethylbenzoyl)phosphate, or α-ketoglutaric acid.

6. The organic hydrogel electrolyte according to claim 1, characterized in that, In step S2, in the first gradient precursor solution closest to the negative electrode, the mass of vinylphosphonic acid monomer added is 0.5%-3.0% of the mass of acrylamide, the mass of zwitterionic monomer added is 10%-20% of the mass of acrylamide, and the mass of crosslinking agent added is 0.5%-1.5% of the mass of acrylamide. In the precursor solution of the last gradient closest to the positive electrode, the added mass of vinylphosphonic acid monomer is 0%-0.2% of the mass of acrylamide, the added mass of zwitterionic monomer is 0%-5% of the mass of acrylamide, and the added mass of crosslinking agent is 0.05%-0.30% of the mass of acrylamide. In the precursor solutions between the two gradients mentioned above, the concentrations of these three raw material components decrease sequentially from the negative electrode to the positive electrode.

7. The organic hydrogel electrolyte according to claim 1, characterized in that, In step S3, the surface treatment solution containing vinylphosphonic acid monomer uses a mixture of water and ethanol as a solvent, the mass fraction of vinylphosphonic acid monomer is 0.1%-2.0%, and the volume ratio of water to ethanol is 1:4-4:

1.

8. The organic hydrogel electrolyte according to claim 1, characterized in that, In step S4, the thickness of the wet film after coating with the first gradient precursor solution is 50-150 μm.

9. The organic hydrogel electrolyte according to claim 1, characterized in that, In steps S4 and S6, the pre-curing and overall photocuring use wavelengths of 320-405 nm and irradiances of 5-30 mW / cm², respectively. 2 The light source is used for irradiation; in step S4, the irradiation time for pre-curing is 20-60 s; in step S6, the overall curing time is 5-15 min.

10. The organic hydrogel electrolyte according to claim 1, characterized in that, In step S6, after the precursor solutions of all gradients are photocured, the total thickness of the resulting organic hydrogel electrolyte is 0.50-1.50 mm. When performing EDS line scanning or XPS depth analysis along the thickness direction from the negative electrode to the positive electrode, the signal intensity of P and S elements gradually decreases.